Potent antiplasmodial extracts and fractions from Terminalia mantaly and Terminalia superba - Mbouna, Cedric D. J. (Malar J, 2018)
BACKGROUND: The emergence and spread of malaria parasites resistant to artemisinin-based combination therapy stresses the need for novel drugs against malaria. Investigating plants used in traditional medicine to treat malaria remains a credible option for new anti-malarial drug development. This study was aimed at investigating the antiplasmodial activity and selectivity of extracts and fractions from Terminalia mantaly and Terminalia superba (Combretaceae) that are used in Cameroon to treat malaria. METHODS: Twelve methanolic (m) and water (w) extracts obtained by maceration of powdered dried leaves (l), stem bark (sb) and root (r) of Terminalia mantaly (Tm) and Terminalia superba (Ts) and 12 derived fractions of hexane, chloroform, ethyl acetate and 4 final residues of selected extracts were assessed for antiplasmodial potential in vitro against the chloroquine-resistant PfINDO and the chloroquine-sensitive Pf3D7 strains of Plasmodium falciparum using the SYBR green I-based fluorescence assay. The cytotoxicity of potent extracts and fractions was evaluated in vitro using the MTT assay on HEK239T cell line. RESULTS: The antiplasmodial IC(50) of extracts from both plants ranged from 0.26 to > 25 µg/mL. Apart from the extracts Tmrm and Tsrw that exerted moderate antiplasmodial activities (IC(50): 5–20 µg/mL) and Tmrw that was found to be non-active at the tested concentrations (IC(50) > 25 µg/mL), all other tested crude extracts exhibited potent activities with IC(50) < 5 µg/mL. The aqueous extracts from the stem bark of Terminalia mantaly (Tmsbw) and the leaf of Terminalia superba (Tslw) displayed the highest antiplasmodial activities (IC(50): 0.26–1.26 µg/mL) and selectivity (SI > 158) on both resistant PfINDO and sensitive Pf3D7 strains. Four fractions upon further extraction with chloroform and ethyl acetate (TmlwChl, TmsbwChl, TmsbwEA, TsrmEA) afforded from three selected crude extracts (Tmlw, Tmsbw, Tsrm) exhibited highly potent activities against both P. falciparum strains (IC(50) < 2 µg/mL) and high selectivity (SI > 109). CONCLUSIONS: The results achieved in this work validate the reported traditional use of Terminalia mantaly and Terminalia superba to treat malaria. Moreover, the highly potent and selective fractions warrant further investigation to characterize the active antiplasmodial principles and progress them to rodent malaria models studies if activity and selectivity are evidenced.